Contrasting Vaginal Bacterial Communities Between Estrus and Non-estrus of Giant Pandas (Ailuropoda melanoleuca) - Yue, Chanjuan; Luo, Xue; Ma, Xiaoping; Zhang, Dongsheng; Yan, Xia; Deng, Zeshuai; Li, Yunli; Liu, Yuliang; An, Junhui; Fan, Xueyang; Li, Lin; Su, Xiaoyan; et al. (Frontiers in Microbiology, 2021)
Bacterial infection and imbalance of bacterial community in the genitourinary system of giant panda could affect the reproductive health. In severe cases, it can also lead to abortion. In this study, thirteen of vaginal secretions in the estrue (E) group and seven of vaginal secretions in the non-estrue (NE) group were used to study the composition and diversity of vaginal bacterial communities between estrus and non-estrus by 16S rRNA gene sequencing analysis. The results showed that the vaginal microbiome in giant pandas shared the same top five abundant species between estrus and non-estrus at the phylum level. However, the vaginal microbiome changed significantly during estrus at the genus level. In top ten genera, the abundance of Escherichia, Streptococcus and Bacteroides in the E group was significantly higher than that in the NE group (P<0.05); Azomonas, Porphyromonas, Prevotella, Campylobacter and Peptoniphilus in the NE group was significantly higher than that in the E group (P <0.05). The richness and diversity of vaginal microbiome in giant panda on estrus were significantly lower than those on non-estrus (P < 0.05). It is noteworthy that the abundance of Streptococcus, Escherichia and Bacteroides of vagina in giant pandas maintained low abundance in the daily. Whereas, they increased significantly during estrus period, which may play an important role in female giant pandas during estrus period. It was hypothesized that hormones may be responsible for the changes in the vaginal microbiome of giant pandas between estrus and no-estrus stages.